Fifth-week immunogenicity and safety of anti-SARS-CoV-2 BNT162b2 vaccine in patients with multiple myeloma and myeloproliferative malignancies on active treatment: preliminary data from a single institution - Pimpinelli, Fulvia; Marchesi, Francesco; Piaggio, Giulia; Giannarelli, Diana; Papa, Elena; Falcucci, Paolo; Pontone, Martina; Di Martino, Simona; Laquintana, Valentina; La Malfa, Antonia; Di Domenico, Enea Gino; Di Bella, Ornella; et al. (Journal of hematology and oncology, 2021)
Safety and immunogenicity of BNT162b2 mRNA vaccine are unknown in hematological patients; both were evaluated prospectively in 42 patients with multiple myeloma (MM) and 50 with myeloproliferative malignancies (MPM) (20 chronic myeloid leukemias and 30 myeloproliferative neoplasms), all of them on active anti-cancer treatment, in comparison with 36 elderly controls not suffering from cancer. Subjects serologically and/or molecularly (by nasal/throat swab) positives at basal for SARS-CoV-2 were excluded. Primary endpoint was to compare titers of neutralizing anti-SARS-CoV-2 IgG and seroprotection rates among the cohorts at 3 and 5 weeks from first dose. Titration was done using LIAISON® SARS-CoV-2 S1/S2 IgG test, a quantitative chemiluminescent immunoassay approved by FDA on the basis of robust evidences of concordance (94.4%) between the test at cutoff of 15 AU/mL and the Plaque Reduction Neutralization Test 90% at 1:40 ratio. Cutoff of 15 AU/mL was assumed to discriminate responders to vaccination with a protective titer. Cohorts were compared using Fisher' exact test and the Mann-Whitney test as appropriated. Geometric mean concentrations (GMCs), geometric mean ratios and response rates after 1st and 2nd dose were compared in each cohort by Wilcoxon and McNemar tests, respectively. At 5 weeks, GMC of IgG in elderly controls was 353.3 AU/mL versus 106.7 in MM (p = 0.003) and 172.9 in MPM patients (p = 0.049). Seroprotection rate at cutoff of 15 AU/mL was 100% in controls compared to 78.6% in MM (p = 0.003) and 88% in MPM patients (p = 0.038). In terms of logarithm of IgG titer, in a generalized multivariate linear model, no gender effect was observed (p = 0.913), while there was a significant trend toward lower titers by increasing age (p < 0.001) and in disease cohorts with respect to controls (MM: p < 0.001 and MPM: p < 0.001). An ongoing treatment without daratumumab was associated with higher likelihood of response in MM patients (p = 0.003). No swabs resulted positive on each time point. No safety concerns were observed. BNT162b2 has demonstrated to be immunogenic at different extent among the cohorts. Response was 88% and robust in MPM patients. MM patients responded significantly less, particularly those on anti-CD38-based treatment. These latter patients should be advised to maintain masks and social distancing regardless of vaccination status, and their cohabiting family members need to be vaccinated in order to reduce the risk of contagion from the family. Additional boosters and titer monitoring could be considered. Trial registration Study was formally approved by the IRCCS Central Ethical Committee of Regione Lazio in January 2021 (Prot. N-1463/21).